2017
DOI: 10.1093/jhered/esx044
|View full text |Cite
|
Sign up to set email alerts
|

Range-Wide Snow Leopard Phylogeography Supports Three Subspecies

Abstract: The snow leopard, Panthera uncia, is an elusive high-altitude specialist that inhabits vast, inaccessible habitat across Asia. We conducted the first range-wide genetic assessment of snow leopards based on noninvasive scat surveys. Thirty-three microsatellites were genotyped and a total of 683 bp of mitochondrial DNA sequenced in 70 individuals. Snow leopards exhibited low genetic diversity at microsatellites (A N = 5.8, H O = 0.433, H E = 0.568), virtually no mtDNA variation, and underwent a bottleneck in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 88 publications
5
42
0
Order By: Relevance
“…Modern tigers are characterized by an overall reduced genomic variability yet a highly differentiated population genetic partition. Only 196 variable sites were found across the mitogenome (nucleotide diversity p = 0.00247), substantially fewer than the numbers found in other Panthera species [18][19][20][21]; however, 173 were subspecies diagnostic or specific single-nucleotide variation (SNV) sites, including 17 in P.t. altaica, 39 in P.t.…”
Section: Genomic Diversity In Tigersmentioning
confidence: 86%
“…Modern tigers are characterized by an overall reduced genomic variability yet a highly differentiated population genetic partition. Only 196 variable sites were found across the mitogenome (nucleotide diversity p = 0.00247), substantially fewer than the numbers found in other Panthera species [18][19][20][21]; however, 173 were subspecies diagnostic or specific single-nucleotide variation (SNV) sites, including 17 in P.t. altaica, 39 in P.t.…”
Section: Genomic Diversity In Tigersmentioning
confidence: 86%
“…Except for four Nepalese samples from the eastern border, there is no sampling from the rest of the Nepali Himalaya and the NW Indian Himalaya, between the western border of Nepal and the Karakorum mountain range. The proposed boundary between two of the putative subspecies reported by Janecka et al (2017), coincides with this sampling gap, which is problematic for the interpretation of the data. Similarly, samples were only collected from the western Tien Shan range, with no samples from the mountain ranges to the west and south of the Dzungarian Basin, which has been highlighted as a region of importance for understanding population connectivity for snow leopard (Riordan et al 2015).…”
Section: Samplingmentioning
confidence: 90%
“…Similarly, samples were only collected from the western Tien Shan range, with no samples from the mountain ranges to the west and south of the Dzungarian Basin, which has been highlighted as a region of importance for understanding population connectivity for snow leopard (Riordan et al 2015). Janecka et al (2017) also present this area as a boundary between putative subspecies, which we again think should be interpreted with a degree of caution based on the distribution of samples used. Given the difficulty of collecting samples in this region of the world we do not criticise the authors for these gaps, it should, however, be acknowledged that they may be contributing to the pattern of divergence shown since the authors are primarily relying on the evidence from genetic markers to make their claim, this is relevant, if potentially difficult to overcome.…”
Section: Samplingmentioning
confidence: 99%
“…This confirms the results from a recent range-wide snow leopard phylogeographic study, which found three clusters corresponding to the geographic subspecies Panthera uncia irbis (Mongolia), Panthera uncia uncia (India, Pakistan, Tajikistan, and Kyrgyzstan), and Panthera uncia uncioides (Qinghai, Tibet, Bhutan, and Nepal). Within each subspecies, genetic differentiation was very low, in particular among four individuals from Kyrgyzstan belonging to the subspecies Panthera uncia uncia 22 .…”
Section: Diachronic Monitoring Of Individualsmentioning
confidence: 97%